1974
DOI: 10.1161/01.res.34.5.682
|View full text |Cite
|
Sign up to set email alerts
|

Nature of the Gap Phenomenon in Man

Abstract: The atrioventricular (AV) gap phenomenon occurs when the effective refractory period of a distal site is longer than the functional refractory period of a proximal site and when closely coupled stimuli are delayed enough at the proximal site to allow distal site recovery. According to previous studies, in type 1 gap, the distal site of block is distal to the His bundle (ventricular specialized conduction system) and the proximal site of block is in the AV node. In type 2 gap, both the proximal and the distal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1975
1975
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…This explanation did not require the existence of proximal conduction system duality. Many examples of anterograde (Agha et al, 1973;Gallagher et al, 1973;Wu et al, 1974) and retrograde gap (Akhtar et al, 1974a, b) have now been described and classified in terms of sites of distal block and proximal delay (Damato et al, 1976) and Durrer's (1968) original hypothesis still awaits confirmation. Electrophysiological evidence of AV nodal dual conduction pathways is provided by the construction of an anterograde conduction curve (Moe et al, 1956).…”
Section: Discussionmentioning
confidence: 99%
“…This explanation did not require the existence of proximal conduction system duality. Many examples of anterograde (Agha et al, 1973;Gallagher et al, 1973;Wu et al, 1974) and retrograde gap (Akhtar et al, 1974a, b) have now been described and classified in terms of sites of distal block and proximal delay (Damato et al, 1976) and Durrer's (1968) original hypothesis still awaits confirmation. Electrophysiological evidence of AV nodal dual conduction pathways is provided by the construction of an anterograde conduction curve (Moe et al, 1956).…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al (1974) predicted that a gap between the atria and the AV node would occur more easily at higher rates. Shorter cycle lengths tend to shorten the effective refractory period of the atrium and lengthen the effective refractory period of the AV node (Wit et al,I97oa) and AV block will occur more easily.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Wu et al (I974) showed that this classification was an over simplification of the gap phenomenon and that it could also occur at other levels in the conducting system from the atria to the ventricles. The purpose of this paper is to present two cases which tend to reinforce the view of Wu et al (1974).…”
mentioning
confidence: 90%
“…For example, abolishment of a gap between the AV node and His Purkinje system was demonstrated by decreasing the cycle length," as well as by the use of ,B-adrenergic blocking agents or digitalis.9 Alternatively, atropine, by altering refractoriness within the AV node, was shown to induce a gap involving the more distal portions of the conduction system,3 while shortening of the cycle length facilitates gap between the atrium and the AV node. 10 Although the phenomenon of a clinical gap is usually associated with conduction block, the prerequisite for the development of PGVS-dependent "gap," as shown in Figures 3 and 4, was the occurrence of a positive slope in the conduction curve (i.e., an increase in the AV nodal conduction time accompanying an increase in the coupling interval). Using this broader criterion, we examined the effect of two agents, atropine and physostigmine, on PGVS-induced "gap."…”
Section: Masking Of the Positive Slope By Changes In The Effectivenesmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13] In all cases, the gap phenomenon was explained in terms of different refractory or conductive properties or both of two consecutive units of the conduction system (e.g., atrium-atrioventricular [AV] node, AV node-bundle of His, bundle of His-His Purkinje system). The prerequisite for the development of the gap phenomenon in most instances was the existence of a distal unit with an effective refractory period longer than the functional refractory period of the proximal unit.…”
mentioning
confidence: 99%